School children's own views, roles and contribution to choices regarding diet and activity in Spain. Issue 1 (13th February 2012) - Lopez‐Dicastillo, O.; Grande, G.; Callery, P.
Abstract Background Behaviours regarding food and activity are learned during childhood and continue throughout life. Children can be very important agents in making decisions concerning their own well‐being and care and their perspective is essential to understanding how they and/or others make choices for them to achieve a healthy lifestyle. However, their perspectives remain under‐researched. This study provides an insight into school children's own perspectives, behaviours and contribution to food and activity choices. Methods The paper reports on the findings from an ethnographic study with 38 Spanish children aged 5–7 years. Information was obtained through participant observations, diaries kept by children and group interviews. Data were analysed using techniques of analytical induction and constant comparison. Results The children who took part in this study described choices about activities with enthusiasm. Children saw activity as a way of learning new things, mastering skills and socializing. They were willing to try and experience new activities and games. However, the activities performed depended on parents' agendas and security issues. In contrast, children reported less interest in and active involvement in food choices. They contributed to family food choices indirectly through the expression of their preferences, not wanting to eat what they disliked or tasting new foods. Conclusion Children had strong preferences and motivations, particularly about activities which could be harnessed in interventions to prevent obesity and promote healthy diet and activity. Parental involvement and commitment is also important both to encourage exercise according to children's interests and active informed food choices, including introduction to unfamiliar foods.